Efeitos da terapia laser de baixa intensidade na regeneração muscular de ratos após criolesão - Rodrigues, Natalia Camargo (Universidade Federal de São Carlos, 2013)
Skeletal muscle injuries from sport activities are usual, but despite the inherent healing capacity of muscle tissue, this process can be impaired depending on the injury extension, what can lead to atrophy, fibroses, pain and functional recovery incomplete, increasing the risks of recurrent lesions. In addition, biophysical and biochemical resources have been studied in an attempt to enhance the muscle regeneration process, as the low level laser therapy (LLLT). Many studies have showed that this therapeutic modality stimulates positives responses during muscle healing process. Thus, two studies were performed with the aim of evaluating the effects of LLLT (InGaAlP 660 nm), with the fluences of 10 J/cm2 and 50 J/cm2, during Tibiales anterior muscle regeneration after cryolesion. Sixty three Wistar rats (3 month of age, ±300 g) were randomly divided into 3 groups: injured control group (CG) injured animals without any treatment; treated group, at 10 J/cm2 (G10) and treated group, at 50 J/cm2 (G50). Each group was divided into 3 different subgroups (n=7) and on days 7, 14 and 21 post-injury, were sacrificed. The laser irradiation was performed at a single point and started 48 hours after injury, 5 times per week (each 24 hours), followed by an interval of 48 hours. At the first study, the effects of LLLT were analyzed on the muscle regeneration related on molecular mechanisms involved at repair process. The results showed a downregulation of mRNA Cox-2 expression in all treated groups after 14 and 21 days. On day 7, both treated groups had a downregulation of mRNA Vegf expression, but had a increase after 14 and 21 days of treatment, meanly at 50 J/cm2. The mRNA MyoD expression was upregulated with the higher fluence, in all periods evaluated, and with the lower fluence the MyoD levels increased only after 21 days. The Myogenin expression was downregulated in both treated groups on day 7, and was upregulated with dose of 10 J/cm2 after 21 days. These responses suggest that LLLT can improve the skeletal muscle regeneration through the gene expression stimulation. At the second study, the effects of LLLT were evaluated during muscle regeneration, through histological and immunohistochemical aspects. The treated groups had an inflammatory process modulation after 7 days. On day 14, the treated animals, with both fluences, showed organized new muscle fibers and less granulation tissue. After 21 days of lesion, all groups had complete tissue repair. Moreover, the irradiated groups had less necrosis area at the first experimental period evaluated, and, also had more blood vases quantity after 14 and 21 days, at 50 J/cm2. The immunohistochemistry analysis showed Myogenin expression in all experimental groups after 7 and 14 days, and at day 21st; the immunoexpression was detectable in the control group and in the treated group with lower fluence. Superior MyoD expression appeared in both treated groups during all evaluated periods. Concluding, both fluencies of LLLT played positive effects on muscle repair. Such findings are fundamentals to elucidate the biological and molecular mechanisms involved in the skeletal muscle regeneration.
Keywords: Biotecnologia; Expressão gênica; Imunohistoquímica; Regeneração muscular; Terapia laser de baixa intensidade; Criolesão; Muscle regeneration; Low level laser therapy; Cryolesion; Gene expression; Immunohistochemical; OUTROS